Kicking the (barking) dog effect the moderating role of target attributes on triggered displaced aggression William C. Pedersen, Brad J. Bushman, Eduardo A. Vasquez and Norman Miller. - Pedersen, William C.; Bushman, Brad J.; Vasquez, Eduardo A.; Miller, Norman (2008)
Sometimes aggression is displaced onto a target who is not totally innocent but emits a mildly irritating behaviour called a triggering event. In three experiments, the authors examine stable personal attributes of targets that can impact such triggered displaced aggression (TDA). Lower levels of TDA were directed to targets whose attitudes were similar as compared to dissimilar to those of the actor (Experiment 1) and to targets who were in-group as compared to out-group members (Experiment 2). Conceptually replicating the findings of Experiments 1 and 2, the manipulated valence of the target (viz., liked, neutral, and disliked) functioned in a similar manner, with positive valence serving a buffering function against a triggering action that followed an initial provocation (Experiment 3). The results from all three experiments are consistent with cognitive neo-associationist theory.